ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PEGAWAI DI INSPEKTORAT PROVINSI JAWA TENGAH - Ruli Arioma; Moch Mustam (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2016)
The problem in this research is have not optimum performance of employees at the Inspektorat Provinsi Jawa Tengah. The purpose of this study is to determine how much influence the ability of employees , work interests, leadership, organizational climate, motivation and job satisfaction. Quantitative research methods with explanatory research design. The results of this study indicate that there is a relationship and a positive influence on the ability to work with a correlation coefficient ( r = 0.229 ; KD = 5.24 % ) working interest ( r = 0.217 ; KD = 4.4 % ) , leadership ( r = 0.298 ; KD=8.88% ), organizational climate ( r = 0.385 ; KD = 14.85 % ), motivation ( r = 0.216 ; KD = 4.6 % ) and job satisfaction ( r = 0.243;KD = 5,9 % ) on employee performance. It means if capability more high, the corresponding interests, the better the behavior of its leadership, the more conducive organizational climate, motivation is getting high and job satisfaction is getting high, it make the performance of employees more high than before. Because the factors that affect the performance of employees is the ability, interests of employees, leadership, organizational climate, motivation and job satisfaction then, to improve employee performance can be done by improving the ability, to adjust interest in his work, improve the behavior of the leadership, make organizational climate condusif, improve motivation and maintain employee satisfaction and provide functional training to employees and PIM training on leadership, leaders also need to create a conducive organizational climate by providing specific direction and giving a clear time limit on each job so that it can improve employee performance.